2016
DOI: 10.1111/joa.12450
|View full text |Cite
|
Sign up to set email alerts
|

Biorhythms, deciduous enamel thickness, and primary bone growth: a test of the Havers‐Halberg Oscillation hypothesis

Abstract: Across mammalian species, the periodicity with which enamel layers form (Retzius periodicity) in permanent teeth corresponds with average body mass and the pace of life history. According to the Havers-Halberg Oscillation hypothesis (HHO), Retzius periodicity (RP) is a manifestation of a biorhythm that is also expressed in lamellar bone. Potentially, these links provide a basis for investigating aspects of a species' biology from fossilized teeth. Here, we tested intra-specific predictions of this hypothesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 58 publications
5
37
0
10
Order By: Relevance
“…While periodicity of striae of Retzius, and their surface expression as perikymata, are thought to be invariant for the individual, it may be that some teeth, particularly deciduous teeth, show different periodicities than do permanent teeth from the same individual. 39 Periodicity is reported to range in humans from 6 to 12 days in permanent teeth but, of these, 95% had periodicities between 7 and 10 days 40 with a mode of 8 days 41 . As yet, Retzius periodicities for H. naledi are unknown.…”
Section: Visualisation and Instruments For Recording Developmental Enmentioning
confidence: 99%
“…While periodicity of striae of Retzius, and their surface expression as perikymata, are thought to be invariant for the individual, it may be that some teeth, particularly deciduous teeth, show different periodicities than do permanent teeth from the same individual. 39 Periodicity is reported to range in humans from 6 to 12 days in permanent teeth but, of these, 95% had periodicities between 7 and 10 days 40 with a mode of 8 days 41 . As yet, Retzius periodicities for H. naledi are unknown.…”
Section: Visualisation and Instruments For Recording Developmental Enmentioning
confidence: 99%
“…The RP values of 4 and 5 reported for deciduous teeth in studies by Mahoney and colleagues (Mahoney, 2011(Mahoney, , 2012Mahoney et al 2016) are certainly possible adult values for RP, as we have observed an RP of 5 in an adult Peruvians from archaeological context (Hogg & Bromage, 2018); therefore the low numbers reported for some deciduous teeth may mean nothing in and of themselves. If the numbers are anomalously low in deciduous teeth, this would be interesting but not relevant to the purported test of the HHO hypothesis by colleagues (Mahoney, 2011, 2012;Mahoney et al 2016) because the HHO model is based upon biological timing recorded in the permanent dentition.…”
Section: Introductionmentioning
confidence: 49%
“…A recent study (Mahoney et al. ) has argued that RP changes during the juvenile period, slowing down with the approach of adulthood; however, this conclusion is based on comparison of a very small sample of deciduous teeth against a much larger sample of permanent teeth drawn from multiple studies (Reid & Dean, ; Smith et al. ), so it is unclear currently if this finding is a statistical artefact.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations